2013
DOI: 10.7763/ijssh.2012.v2.175
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Public Speaking in a Blended Learning Environment

Abstract: Information and communication technologies (ICTs) provide new environment for learning and teaching. Today, apart from a fully face-to-face or online environment, blended learning promises opportunities for teaching and learning to be done in both environments. This paper reports results from an analysis of data collected from students at a Malaysian university. An end-of-semester survey was completed by 40 students taking a Public Speaking course. The survey was conducted to understand students' reactions tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Several students even demonstrated obvious improvement in the use of voice and gestures. The findings on the learning outcomes of RMO2P could complement other intervention designs, such as those that investigated participant perceptions (Balakrishnan & Fatimah, 2014;Murugaiah, 2016) and those that focused on other aspects apart from multimodal skills (Ainol & Zailin, 2012;Hafizoah et al, 2015;Nadzrah et al, 2013).…”
Section: Design Principle 5: Anticipate Multiple Layers Of Integration In the Instructional Designmentioning
confidence: 77%
See 2 more Smart Citations
“…Several students even demonstrated obvious improvement in the use of voice and gestures. The findings on the learning outcomes of RMO2P could complement other intervention designs, such as those that investigated participant perceptions (Balakrishnan & Fatimah, 2014;Murugaiah, 2016) and those that focused on other aspects apart from multimodal skills (Ainol & Zailin, 2012;Hafizoah et al, 2015;Nadzrah et al, 2013).…”
Section: Design Principle 5: Anticipate Multiple Layers Of Integration In the Instructional Designmentioning
confidence: 77%
“…Hafizoah et al (2015) designed a Creative Strategy Learning Model which positively impacted students' thinking and creativity. Blended learning was recommended for speech preparation (Ainol & Zailin, 2012). There were also experimentations with video blogging which improved student perceptions of public speaking skills (Balakrishnan & Fatimah, 2014), and Pecha Kucha which was reported to be conducive for collaboration and developing skills by teachers and students (Murugaiah, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Blackboard-oriented, online dictionary-based method for presenting etymological analysis of new vocabulary also proved to be more effective in developing vocabulary building skills and inducing positive attitudes towards vocabulary learning than traditional teacher-centred and paper dictionary-based vocabulary instruction (Fageeh, 2014). It was also reported by Ibrahim and Yusoff (2012) that the use of wikis in an EFL blended-format course improved the learners' speech delivery and speaking skills.…”
Section: Technology-enhanced Language Learningmentioning
confidence: 90%
“…Ellis et al (2006) suggested a similar range of tools for BL such as video and audio files, discussion boards, chats, and email. Ibrahim and Yusoff (2012) recommended YouTube, podcasts, and Wikis. To provide enhanced BL, teachers can combine several different media types (Joshi, 2012).…”
Section: Teaching Practices and Blended Learningmentioning
confidence: 99%